Student teachers and inquiry-based mathematics instruction: the impact of efficacy, autonomy, and cooperating teacher implementation - Beggs, Meredith (My University, 2026)
Guided by Bandura’s (1989) social cognitive theory, this study examined the relationship between elementary student teachers self-reported implementation of inquiry-based math instruction and four independent variables. The independent variables included student teachers perceived instructional autonomy, personal math teaching efficacy, outcome expectancy, and student teachers’ reporting of their cooperating teachers’ implementation of inquiry-based instruction. The study used a cross-sectional survey design to collect data from n=130 elementary student teachers using a researcher-developed questionnaire consisting of five subscales to measure each of the variables. Results of multiple regression analysis show that cooperating teacher implementation of inquiry-based mathematics instruction was the strongest predictor of student teachers’ implementation of this instructional practice. Findings from this study emphasize the need to develop strong partnerships between educator preparation programs and partner school districts and to intentionally place student teachers in classrooms that demonstrate best practices in math instruction. Additionally, school districts may use the results to emphasize professional development opportunities in mathematics to promote effective practices in cooperating teachers who will eventually influence the practices of novice teachers.
Keywords: Inquiry-based mathematics instruction; Inquiry-based math instruction; Student teachers; Instructional autonomy; Math teaching efficacy; Cooperating teacher instruction